PPR Protein BFA2 Is Essential for the Accumulation of the atpH/F Transcript in Chloroplasts - Zhang, Lin; Zhou, Wen; Che, Liping; Rochaix, Jean-David; Lu, Congming; Li, Wenjing; Peng, Lianwei (Frontiers in Plant Science, 2019)
As a fascinating and complicated nanomotor, chloroplast ATP synthase comprises nine subunits encoded by both the nuclear and plastid genomes. Because of its uneven subunit stoichiometry, biogenesis of ATP synthase and expression of plastid-encoded ATP synthase genes requires assistance by nucleus-encoded factors involved in transcriptional, post-transcriptional, and translational steps. In this study, we report a P-class pentatricopeptide repeat (PPR) protein BFA2 (Biogenesis Factor required for ATP synthase 2) that is essential for accumulation of the dicistronic atpH/F transcript in Arabidopsis chloroplasts. A loss-of-function mutation in BFA2 results in a specific reduction of more than 3/4 of chloroplast ATP synthase, which is likely due to the absence of dicistronic atpH/F transcript. BFA2 protein contains 22 putative PPR motifs and exclusively localizes in the chloroplast. Bioinformatics and EMSA (Electrophoretic Mobility Shift Assays) analysis showed that BFA2 binds to the consensus sequence of the atpF-atpA intergenic region in a sequence-specific manner. However, translation initiation of the atpA was not affected in the bfa2 mutant. Thus, we proposed that the chloroplast PPR protein BFA2 mainly acts as barrier to prevent the atpH/F transcript degradation by exoribonucleases by binding to the consensus sequence of the atpF-atpA intergenic region.